(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
The purpose of the research is to describe and analyze the development of transport terminology, to study its features, ways and methods of terminological nomination in the time frame of a particular historical period. The theoretical significance of the article consists in: the description of transport terminology from the standpoint of a single system of interrelated terminological fields that combine the concepts of a number of areas related to transport; analysis of the process of standardization of transport terms; designation and description of factors influencing the expansion and development of transport terminology; designation of the process of forming a single language of international mixed messages and transport and logistics information exchange in transport.